Analysis of the virome associated to grapevine downy mildew lesions reveals new mycovirus lineages. Issue 2 (30th November 2020) - Chiapello, M; Rodríguez-Romero, J; Ayllón, M A; Turina, M
Abstract: The obligatory biotrophic oomycetes Plasmopara viticola is the causal agent of downy mildew, a destructive disease of grapevine worldwide. So far, chemical fungicides are widely employed to limit this pathogen, but their adverse effects are stimulating the quest for environmentally friendly alternative approaches. Here, we report on the search for mycoviruses that might be later developed as biocontrol agents for this pathogen. Symptomatic leaves were collected from various regions in Spain and Italy and mycelia associated to leaf lesions was harvested. Total RNA extractions were depleted of rRNA and metatranscriptomes were generated using a high-throughput sequencing approach. The virome associated to leaf lesions was then characterized through a bioinformatic pipeline relying on blast searches against current viral databases. Here, we present an inventory of 283 new RNA viruses: 222 positive strand RNA viruses, 29 negative strand RNA viruses, 27 double-stranded RNA viruses and 5 ORFan virus RdRP segments, which could not be reliably assigned to any existing group in the Riboviria . In addition to ORFan viruses, we found other surprising new evolutionary trajectories in this wide inventory of viruses. The most represented viruses in our collection are those in phylum Lenarviricota, and, among them, a group of mycovirus segments distantly related to narnaviruses, but characterized by a polymerase palm domain lacking subdomain C, with the putative GDD catalytic triad. We also provided evidence of a strict association between two RNA segments that form a new mycovirus clade of positive strand RNA in the phylum Kitrinoviricota, order Martellivirales . In the phylum Negarnaviricota, we report for the first time in the order Mononegavirales a clade of viruses that is ambisense, a feature that so far was present only in the order Bunyavirales . Furthermore, in the same phylum we detected the widespread occurrence and abundant accumulation in our libraries of a distinct mycovirus clade distantly related to the Muvirales and Goujanvirales orders, which so far include only viruses infecting invertebrates. Possible new oomycetes-specific virus clades are also described in the phylum Duplornaviricota . These data greatly expand the evolutionary history of mycoviruses adding new layers of diversity to the realm Riboviria .